Effective Teachers of Academic Writing in an EFL Context: Students and Teachers Beliefs - Zakzak, Lama Saleem (2016)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Lama Saleem Zakzak entitled, "Effective Teachers of Academic Writing in an EFL Context: Students and Teachers Beliefs," submitted January 2016. Thesis advisor is Dr. Ahmad Al-Issa. Soft and hard copy available.